Factors Associated with Nurses’ Intention to Leave Their Jobs after the Fukushima Daiichi Nuclear Power Plant Accident - Sato, Yoshinobu; Hayashida, Naomi; Orita, Makiko; Urata, Hideko; Shinkawa, Tetsuko; Fukushima, Yoshiko; Nakashima, Yumiko; Kudo, Takashi; Yamashita, Shunichi; Takamura, Noboru (PloS one, 2015)
We conducted a survey among nurses who were working at the Fukushima Medical University Hospital at the time of the Fukushima Daiichi Nuclear Power Plant accident to clarify the factors associated with their intention to leave their jobs during the radiation emergency. We asked 345 nurses (17 men and 328 women) about their intention to leave their jobs after the accident. We also asked about relevant factors including the participants' demographic factors, living situation, working status, and knowledge of radiation health effects. We found that living with preschoolers (OR = 1.87, 95%CI: 1.02-3.44, p = 0.042), anxiety about life in Fukushima City after the accident (OR = 5.55, 95%CI: 1.18-26.13, p = 0.030), consideration of evacuation from Fukushima after the accident (OR = 2.42, 95%CI: 1.45-4.06, p = 0.001), consideration of the possible radiation health effects in children (OR = 1.90, 95%CI: 1.02-3.44, p = 0.042), and anxiety about relationships with colleagues in the hospital after the accident (OR = 3.23, p = 0.001) were independently associated with the nurses' intention to leave their jobs after the accident. On the other hand, the percentage of nurses with knowledge on radiation health effects was relatively low among those who had the intention to leave the job and among those who did not have the intention to leave the job after the accident, with no significant differences between the two groups. Our results suggest the need for an education program for nurses regarding radiation health effects.